Alpha-Mangostin-Loaded Transferrin-Conjugated Lipid-Polymer Hybrid Nanoparticles: Development and Characterization for Tumor-Targeted Delivery - Intouch Sakpakdeejaroen; Patcharaporn Muanrit; Sumalee Panthong; Srisopa Ruangnoo (The Scientific World Journal)
Alpha-mangostin, a natural xanthone mainly extracted from the pericarp of Garcinia mangostana, has been shown to have promising anticancer properties in many types of cancer. However, the therapeutic potential of α-mangostin has been limited so far due to its poor aqueous solubility and low oral bioavailability, which limited its biopharmaceutical applications. Furthermore, α-mangostin failed to specifically reach tumors at a therapeutic concentration due and rapid elimination in vivo. We hypothesized that this drawback could be overcome by loading the drug within a delivery system conjugated to transferrin (Tf), whose receptors are overexpressed on many cancer cells and would enhance the specific delivery of α-mangostin to cancer cells, thereby enhancing its therapeutic efficacy. The objectives of this study were therefore to prepare and characterize transferrin-conjugated lipid-polymer hybrid nanoparticles (LPHN) entrapping α-mangostin, as well as to evaluate their therapeutic efficacy in vitro. We successfully prepared α-mangostin loaded LPHN using a one-step nanoprecipitation method with high drug entrapment efficiency. The conjugation of Tf to the LPHN was achieved by using the thiol–maleimide “click” reaction, leading to an increase in the particle hydrodynamic size of Tf-LPHN compared to that of unconjugated (control) LPHN (Ctrl-LPHN). Both Tf-LPHN and Ctrl-LPHN were bearing negative surface charges. Tf-LPHN and Ctrl-LPHN exhibited a sustained release of α-mangostin at pH 7.4, following an initial burst release, unlike rapid release of drug solution. The entrapment of α-mangostin in the LPHN led to an increase in α-mangostin uptake by cancer cells, and thus improved its antiproliferative activity compared to that observed with the drug solution. In conclusion, α-mangostin entrapped in the Tf-LPHN is therefore a highly promising therapeutic system that should be further optimized as therapeutic tools for cancer treatment.